2023
DOI: 10.28991/esj-2023-07-02-020
|View full text |Cite
|
Sign up to set email alerts
|

Climatic Factor Differences and Mangosteen Fruit Quality between On- and Off-Season Productions

Abstract: The objective of this study was to investigate the differences in climatic factors and fruit quality between on- and off-season production periods. Climate, soil, and mangosteen measurements were all studied during on- and off-season production. We chose 40 mangosteen trees and observed flowering and fruit set rates over two production periods. The results showed that the number of flowers per branch, the number of fruits per branch, the circumference of fruits, and the fruit weight were higher during the on-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…The period of bearing fruits: on season. At the eastern areas, on season period starts from September and harvest time starts from April to June [39] Fruit production: 300 kg/tree/year. Productivity of Gunungsari mangosteen is higher than the average productivity of mangosteen in Indonesia in 2021 about 112.…”
Section: Yearmentioning
confidence: 99%
See 1 more Smart Citation
“…The period of bearing fruits: on season. At the eastern areas, on season period starts from September and harvest time starts from April to June [39] Fruit production: 300 kg/tree/year. Productivity of Gunungsari mangosteen is higher than the average productivity of mangosteen in Indonesia in 2021 about 112.…”
Section: Yearmentioning
confidence: 99%
“…34 kg/tree [7]. When compared with mangosteen production in the off season, breeding mangosteen in the off-season produced heavier fruits [39] The main characteristic of Gunungsari mangosteen is the seed which soft or tender. Moreover, the seeds are flat-shaped and there are not even seeds inside the aril (flesh of fruit).…”
Section: Yearmentioning
confidence: 99%
“…With a colossal planting area of 67,151 hectares and an annual yield of 340,000 tons, Thailand stands unchallenged as the world's top mangosteen supplier, with China receiving most of its exports. [22]. Mangosteen is a perennial plant with a dark brown bark that produces purple-red skin fruit with edible white, soft, juicy, sweet, and acidic pulp [23].…”
Section: Mangosteen Biologymentioning
confidence: 99%
“…At the same time, the phloem plays an essential role in fruit expansion, carrying dissolved sugars, acting as an osmotic attractant, drawing water into the developing fruit cells, and contributing to their juiciness [29]. Like other tropical fruits, low soil moisture in a root area induces mangosteen flowering [22]. Soil temperature is important for mangosteen nutrient transformation and uptake by roots, vegetative growth, and reproduction regulated by various factors such as soil color, moisture, compaction, amount of vegetation cover, ambient temperature, and amount of sunlight available [30].…”
Section: Climatic and Soil Parametersmentioning
confidence: 99%
“…In recent years, biochar, an emerging material that serves as a fertilizer, adsorbent, soil improver, and heavy metal chelating agent, has increasingly been reported to improve the structure of the soil microbiome and serve as a carrier of microbial fertilizer [14][15][16][17][18]. Studies have shown that the unique physical and chemical properties of biochar can provide a place for the growth and reproduction of phosphate solubilizing bacteria and promote their phosphate solubilizing activity [19].…”
Section: Introductionmentioning
confidence: 99%